Musik Moderasi: Konsep Bermusik dalam Keberagaman di Kota Kupang, Nusa Tenggara Timur - Relin Yosi Huka; Andrean Tabun (Institut Agama Kristen Negeri Palangka Raya, 2024)
In general, music can live in the community of human life both culturally, ethnically and religiously and develop according to the needs of the culture, ethnicity and religion itself. In a more general context, it can also be interpreted that music can also be a unifying tool in uniting various differences of opinion. Moderation is the concept of adjusting an atmosphere in relation to providing an understanding of equality and balance in interpreting the basics of a good life in pluralism. Pluralism in this context is associated with the growing religious diversity in the city of Kupang, East Nusa Tenggara. Music can unite and become a means of uniting various religions in responding to national contexts that are different but still one. This research takes the concept of moderation in music as a means to provide space for expression in the context of pluralism.